AKSIOLOGI BUDAYA LOKAL JAWA-BALI PADA PROSES KREATIF BERKARYA PELUKIS BALI DI YOGYAKARTA - I Gede Arya Sucitra; Septiana Dwiputri Maharani (Studi Budaya Nusantara, 2019)
ABSTRACT Every human being has aspects of life which include philosophy, belief, science, and art. These four aspects interact and complement each other into one whole system. This research seeks to investigate deeper about the axiological aspects of the acculturation of local cultural values in the interaction of the environment of society (culture) of different ethnic, racial, religious, and local genius values which have a shared awareness of mutual respect, tolerance and “open” to the presence of other cultures. The object of this research material is Balinese artists / painters diaspora who are creative in Yogyakarta, and their formal object is Axiology.By investigating and examining the expression of art and the output of works of art produced by Balinese diaspora painters in Yogyakarta, it can be seen the condition of the development of art, adaptation of cultural values, and the personal abilities of artists as personal and social creatures in mingling and sometimes syncretic. Artists as part of cultural support, certainly can not be separated from the various influences that are in the surrounding environment. Theory of ethics, aesthetics, and habitus become a strong capital to see the 'touch' and the mix of local cultural values between artists and the local culture that they inhabit, so that it will look at how social relations and reflections of visual relations in the work. Researching and observing the development of art through the path of creation, indeed leads us to the axiology dimension of unique and personal ethical and aesthetic values. Each artist has an apparently autonomous world and the application of ethical values in the process of his work but still able to ground themselves to adapt, tolerance and multicultural life. ABSTRAKSetiap diri manusia memiliki aspek-aspek kehidupan yang meliputi filsafat, kepercayaan, ilmu, dan seni. Keempat aspek tersebut saling berinteraksi dan saling melengkapi menjadi satu sistem yang utuh. Penelitian ini berupaya menyelidiki lebih dalam mengenai aspek aksiologi akulturasi nilai-nilai budaya lokal pada interaksi lingkungan masyarakat (kebudayaan) yang berbeda-beda suku, ras, agama, dan nilai local genius-nya yang mana memiliki kesadaran bersama untuk saling menghormati, toleran dan ‘terbuka’ atas kehadiran budaya lain. Objek material penelitian ini yakni perupa/pelukis perantauan Bali yang proses kreatif di Yogyakarta, dan objek formalnya yakni Aksiologi.Dengan menyelidiki dan meneliti ekspresi kesenian serta luaran karya seni yang dihasilkan olehpelukis perantauan Bali di Yogyakarta, maka dapat dilihat kondisi perkembangan berkesenian, adaptasi nilai-nilai budaya, dan kemampuan personal perupa sebagai diri pribadi dan makhluk sosial dalam berbaur dan terkadang sinkretis. Perupa sebagai bagian dari penyangga kebudayaan, tentu tidak bisa terlepas dari berbagai pengaruh yang berada di lingkungan sekitarnya. Teori etika, estetika, dan habitus menjadi modal yang kuat untuk melihat ‘persentuhan’ dan bauran nilai budaya lokal antara perupa dan budaya setempat yang mereka diami, sehingga akan tampak bagaimana relasi sosial dan refleksi relasi visual dalam karya.Meneliti dan mengamati perkembangan seni rupa melalui jalur penciptaan, memang mengantarkan kita pada dimensi aksiologi nilai etika dan estetika yang unik dan personal. Setiap perupa memiliki dunia rupanya yang otonom serta pengendapaan nilai etika dalam proses berkaryanya namun tetap mampu membumikan diri untuk beradaptasi, toleransi dan hidup multikultur.